A Cyclist’s Eye View of Rural Sustainability and Governance in Canada - John Martin (Commonwealth Journal of Local Governance, 2012)
The study aims to discover and research what Canadian and Australian rural communities have in common. In both countries, rural communities are located in federations similar in structure and function, with provinces/states having considerable authority over these places. Governments are often challenged to provide equitable services to all places, especially in rural communities. Yet these communities continue to survive often facing the most challenging demographic, economic and environmental circumstances. In this comparative research, John and Alistair will ask what it is about these places, people and institutions that sustain them over time addressing the key issue of how their past, current economic fortunes, social networks and public institutions work together to ensure their sustainability.